Occupational Burnout on University Teachers Through the Confirmatory Factorial Model - Fuster-Guillén, Doris (2019)
The research addresses occupational burnout on university teachers, understood as progressive loss of energy, emotional exhaustion, fatigue, irritability, negative attitudes and feelings of dissatisfaction. The purpose of the study was to compare the presence of job burnout on teachers of the School of Education and Electronic Engineering from a Public University of Peru. It was developed according to principles of quantitative approach, transactional non-experimental design, and type of substantive, descriptive-comparative research. The sample was made up of 125 teachers from both faculties to which the Occupational Attendance Scale-EDO was administered. This instrument presented the required validity and reliability. The results obtained through the confirmatory factor model of structural equations, estimated through the asymptotic free distribution method, led to the conclusion that the teachers from the School of Education report greater emotional wear than teachers of the School of engineering.